Self-assembled vertically aligned gold nanorod super-lattices for ultra-high sensitive detection of molecules - Apte, Amey; Bhaskar, Prashant; Das, Raja; Chaturvedi, Smita; Poddar, Pankaj; Kulkarni, Sulabha (Nano Research, 2015)
We show that self-assembled vertically aligned gold nanorod (VA-GNRs) superlattices can serve as probes or substrates for ultra-high sensitive detection of various molecules. D-glucose and 2,4,6-trinitrotoluene (TNT) have been chosen as model systems due to their very low Raman cross-sections (5.6 x 10(-30) cm(2).molecule(-1).sr(-1) for D-glucose and 4.9 x 10(-31) cm(2). molecule(-1).sr(-1) for TNT) to show that the VA-GNR superlattice assembly offers as low as yoctomole sensitivity. Our experiment on mixed samples of bovine serum albumin (BSA) and D-glucose solutions demonstrate sensitivity for the latter, and the possible extension to real samples. Self-assembled superlattices of VA-GNRs were achieved on a silicon wafer by depositing a drop of solvent containing the GNRs and subsequent solvent evaporation in ambient conditions. An additional advantage of the VA-GNR monolayers is their extremely high reproducible morphology accompanied by ultrahigh sensitivity which will be useful in many fields where a very small amount of analyte is available. Moreover the assembly can be reused a number of times after removing the already present molecules. The method of obtaining VA-GNRs is simple, inexpensive and reproducible. With the help of simulations of monolayers and multilayers it has been shown that superlattices can achieve better sensitivity than monolayer assembly of VA-GNRs.
Keywords: Nanostructures; Raman spectroscopy; self-assemblies; sensors; superlattices

Tunable band gap and coercivity of bismuth ferrite-polyaniline core-shell nanoparticles: the role of shell thickness - Chaturvedi, Smita; Das, Raja; Poddar, Pankaj; Kulkarni, Sulabha (RSC Advances, 2015)
We report a tunable band gap of bismuth ferrite-polyaniline core-shell nanoparticles from 2.24 to 1.98 eV and the variation of coercivity from 118 to 100 Oe, by varying the thickness of the polyaniline shell. Bismuth ferrite nanoparticles were synthesized via a chemical route and coating of polyaniline was achieved by a double surfactant layer technique. Coating of polyaniline introduced oxygen vacancies, local distortions and microstrains in the bismuth ferrite lattice which resulted in a change in the Fe-O-Fe bond angle of the bismuth ferrite lattice. This is confirmed with structural analysis tools i.e. X-ray Diffraction, Fourier Transform Infrared Spectroscopy and Raman spectroscopy. Moreover, the absorption of light around 600 nm is increased and photoluminescence emission around 430 nm is decreased, as the thickness of shell is increased, which also indicates the changes in optical properties due to variation in shell thickness. Thus tunability of the band gap and coercivity is achieved as a function of shell thickness in bismuth ferrite-polyaniline core-shell nanoparticles.